PRAGMATIC MECHANISMS OF IMPLICATURE IN LINGUISTICS (SCIENCE TIME JOURNAL, 2026)
This study explores the concept of implicature within the framework of pragmatics, focusing on its classification and communicative functions. It examines how speakers convey implied meanings beyond literal expressions and analyzes the main types of implicature, including conversational and conventional implicature. Using a qualitative approach, the research investigates examples from everyday communication and academic discourse to identify patterns of implicit meaning. The findings reveal that implicature plays a crucial role in achieving communicative efficiency, politeness, and contextual adaptability. The study also highlights challenges in interpreting implicature, particularly for non-native speakers, and emphasizes its importance in developing pragmatic competence.